Shariah mode of adjudication: Distinctive features vis-à-vis modern systems - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas; Laluddin, Hayatullah (2019)
Modern discourse on adjudication has been made against the backdrop of the two dominant Western models of inquisitorial trial of the French Civil law and adversarial trial of Anglo-American Common law. The fundamental feature of inquisitorial system is that it is that the judge who has the overarching role in adjudicating, while unique feature of adversarial system is that it is disputant-centric. As to which of the models Islamic mode of adjudication fits, opinion varies. Some comparative scholars assimilate it with adversarial model whilst others see it akin to inquisitorial model or having the features of both. This paper, however, argues that the Shariah mode of criminal trial though resembling some features of both, has certain unique features of its own- in view of its religiously colored conception of crime, notion of judicial function, methods and standard of proof and the role of attorney, which defies equation with such models.